Educational level of parents and its relationship to the level of achievement of children – A field study on Al-Sayfah area in Muscat Governorate - sultanate of Oman – - Al Jabri, Sulaiman Saoud Younis (Journal of Educational and Psychological Sciences, 2021)
The study aimed to clarify the relationship between the educational level of parents and the achievement level of children Research using the descriptive analytical method and using the questionnaire as a tool for data collection. The study sample consisted of (35) guardians from Al-Sifah area in Muscat Governorate. They were divided into 26 educated and 9 uneducated individuals. The results of the research indicated a relationship between the educational level of parents and the achievement level of children. The researcher reached the importance of providing cultural media that develop the talents of children, creating an appropriate study atmosphere and instilling positive ideas and trends in children, which hinder their achievement.